Survey of the Internet of things operating system security - Anni PENG; Wei ZHOU; Yan JIA; Yuqing ZHANG (Tongxin xuebao)
With the rapid popularization and wide application of the Internet of things (IoT),the security problems of IoT operating system,which is the essential part,become more and more urgent.Firstly,the famous IoT operating systems and their different features were introduced,then it was compared with present embedded systems.Secondly,On the basis of the survey of research related to IoT operating system,the research was discussed and analyzed from the view of building a comprehensive security system,then security challenges and opportunities which the IoT system faced were pointed out,and the research status of the security of the IoT operating system was summarized.Finally,the promising future study directions in the IoT operating system security field were discussed based on the drawbacks of the existing researches,particularly,the IoT system survival technology as a new research direction was pointed out.